Think like a breadwinner : a wealth-building manifesto for women who want to earn more (and worry less) - Barrett, Jennifer L. (Bluebird, 2021)
"A new kind of manifesto for the working woman, with tips on building wealth and finding balance, as well as inspiration for harnessing the freedom and power that comes from a breadwinning mindset"--